Non-Muslim Students' Perceptions of Islamic Religious Education Learning in class X at YPI Tunas Bangsa High School Palembang - Asep Mulyana; Mumun Munawaroh; Yayat Suryatna; Miftahus Surur; Syafruddin Syafruddin (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The purpose of this study was to determine how the perceptions of non-Muslim students towards learning Islamic religious education in Class X at YPI Tunas Bangsa High School Palembang. The research method used is a quantitative method with descriptive analysis. The total population is four non-Muslim students in class X. The data collection technique uses interviews, observation, documentation and questionnaire techniques. The data analysis technique used quantitative analysis to find out the perception data of non-Muslim students towards Islamic religious education learning by describing its implementation analytically using the percentage model. The results show 1) non-Muslim students like to hear PAI teachers with alternative answers: strongly agree (75%) and agree (25%); 2) non-Muslim students enjoy reading Islamic religious books with alternative answers: strongly agree (50%) and agree (50%); 3) non-Muslim students pay attention to all islamic education activities with alternative answers: agree (25%), unsure (25%) and disagree (50%); 4) non-Muslim students feel that Islamic religious lessons are not boring with alternative answers: strongly agree (25%), agree (50%) and disagree (25%); 5) non-Muslim students find it challenging to do islamic education lesson assignments with alternative answers: strongly agree (75%) and agree (25%); 6) non-Muslim students find islamic education lesson very enjoyable with alternative answers: strongly agree (25%), agree (50%) and disagree (25%); 7) non-Muslim students feel islamic education lesson are easy to understand with alternative answers: agree (75%) and unsure (25%); 8) non-Muslim students are not happy with Islamic religious lessons with alternative answers: unsure (25%) and disagree (75%); 9) religious education provides benefits in the lives of non-Muslim students with alternative answers: strongly agree (25%) and undecided (75%). Based on the results of the questionnaire above, it can be concluded that Islamic religious education has been carried out well, and all students participate in classroom learning. Although non-Muslim students are not required to take Islamic religious lessons, non-Muslim students remain silent in class and often participate in Islamic religious studies.